Achievement of Scientific Literacy Ability of Nunukan Regency Public High School Students - Fitri Wijarini (Asian Journal of Applied Education (AJAE), 2023)
The subjects of this study were students of SMA Negeri Nunukan which consisted of 4 schools namely SMA Negeri 1 Nunukan, SMA Negeri 2 Nunukan, SMA Negeri 1 Nunukan Selatan and SMA Negeri 2 Nunukan Selatan. Determination of the sample using proportionate sampling technique. The data collection instrument used the Scientific Literacy Assessment (SLA) in the form of 20 multiple choice questions with alternative answer choices a, b, c, d, and e. The average achievement of the ability of the four schools was 48.88 in the low category. The average scientific literacy achievement of Nunukan 1 Public High School students was 43.59. SMA Negeri 2 Nunukan of 48.62. SMA Negeri 1 Nunukan Selatan 50.31 and SMA Negeri 2 Nunukan Selatan 53.01.